Insight into Salivary Gland Aquaporins - D’Agostino, Claudia (Cells, 2020)
The main role of salivary glands (SG) is the production and secretion of saliva, in which aquaporins (AQPs) play a key role by ensuring water flow. The AQPs are transmembrane channel proteins permeable to water to allow water transport across cell membranes according to osmotic gradient. This review gives an insight into SG AQPs. Indeed, it gives a summary of the expression and localization of AQPs in adult human, rat and mouse SG, as well as of their physiological role in SG function. Furthermore, the review provides a comprehensive view of the involvement of AQPs in pathological conditions affecting SG, including Sjögren’s syndrome, diabetes, agedness, head and neck cancer radiotherapy and SG cancer. These conditions are characterized by salivary hypofunction resulting in xerostomia. A specific focus is given on current and future therapeutic strategies aiming at AQPs to treat xerostomia. A deeper understanding of the AQPs involvement in molecular mechanisms of saliva secretion and diseases offered new avenues for therapeutic approaches, including drugs, gene therapy and tissue engineering. As such, AQP5 represents a potential therapeutic target in different strategies for the treatment of xerostomia.